Case Series of Hepatosplenic T-Cell Lymphoma: A Rare and Aggressive Disease - Yea Bing Tham; Asral Wirda Ahmad Asnawi; Ngee Siang Lau; Alina Md Fauzi; Sharifah Shahnaz Syed Abd Kadir; Pek Kuen Liew; Sen Mui Tan (Karger, 2024)
Indexed by Scopus